Nest-site selection by golden eagle Aquila chrysaetos (Linnaeus, 1758) (Accipitriformes: Accipitridae) in Janos, Chihuahua, Mexico - Morales-Yañez, Isaac; Rodríguez-Estrella, Ricardo; Gatica-Colima, Ana Bertha (Instituto de Ecología, A.C., 2023)
Knowledge about the selection of nesting sites in birds of prey is essential to carry out any management of a population for its conservation. The golden eagle generally chooses rock walls to nest, and this selection is influenced by the natural and anthropic characteristics of the landscape. In Mexico, studying the golden eagle is important because it has a cultural value as a patriotic symbol and biological role regulating its prey populations. In addition, it is listed under the Official Mexican Norm 059-SEMARNAT-2010 in the category of threatened and there is little published scientific information on its ecology and biology in the country. Therefore, this study determined the habitat variables that influence the selection patterns of golden eagle nesting sites in Janos, Chihuahua; for which nesting sites and sites with similar characteristics without the presence of the golden eagle were located for its characterization. The obtained data was analyzed through generalized linear models, taking the presence and absence of nests as the response variable and the habitat characteristics of the sites as predictor variables. Fifteen nesting sites and sixteen sites without nests were located. Of 15 variables measured, there was only a statistically significant difference in the height of the rock walls (W = 44.5, p = 0.003001). The model with the best fit had an AICc value of 20.6, explaining 68% of the variability of the data and includes the variables of height of the rock walls and the roughness of the terrain, the latter being statistically significant (p = 0.0279). Terrain roughness was present in four of the top five candidate models reflecting the importance of topography for nest site selection that can provide isolation from disturbance for eagles.